The Impact of Quality Management on Reducing Bill Deductions at Operating Theatre Department of Valiasr Hospital A participatory Action Research - Mahnaz Afshari; Alimohammad Mosadeghrad; Mohammad Arab (Tehran University of Medical Sciences, 2017)
Background: The health system of Iran is suffering from resources shortage. The health insurance companies (payers) do not confirm all hospitals' claims (bills) and as a result do not reimburse them completely. Decreasing the amount of these deductions helps healthcare managers to use their resources efficiently. This study aimed to examine the impact of a quality management model on reducing the amount of healthcare insurance deductions at operating theatre department of Valiasr hospital in 2014-2015. Materials and Methods: A participatory action research was used for the intervention. A quality improvement team was established and using the ten-step quality management model improved operational processes at operating theatre department.  Related data were collected before and after the intervention to determine the effect of quality management system on deductions. Results: The average deduction per patient at the beginning of the study was 339572 Rials. Illegible and uncompleted patient's medical records, using wrong codes of surgery and anesthetics in documents and miscalculation were the main reasons of deductions. The reasons for deductions were identified and appropriate solutions were applied to decrease the amount of deductions at operating theatre department. The average deduction per patient at the end of study was 262818 Rials. The amount of deductions has decreased from 6.9 % to 3.8 %. The quality management system helped reduce the amount of deductions by 44.9%. Conclusion: Implementing an appropriate quality management model appropriately helps reduce deductions in hospitals effectively